Model Manajemen Pendidikan Islam Berbasis Nilai untuk Pendidikan Inklusi: Studi Kasus di Hayat School - Nurhasanah, Siti; Izzah, Ikfina Nurul; Ilahiya, Nabila Fadlla; Aminuddin, Muhammad (Jurusan Pendidikan Luar Biasa, 2025)
This study evaluates the inclusive education practices for children with special needs (CSN) at Hayat School, focusing on the integration of Islamic values in educational management. The main objective of this study is to create a fair and inclusive learning environment that accommodates all students without discrimination. A qualitative approach was used in this research, involving interviews, observations, and document analysis to gain an in-depth understanding of the implementation of inclusive education. The findings indicate that challenges in managing inclusive classrooms include the need to stabilize the emotions of students with diverse needs. Teachers face difficulties in maintaining student engagement due to the unstable mood changes of CSN students. Therefore, adopting teaching methods and maintaining a continuous focus are crucial for fostering an inclusive atmosphere. In the student assessment system, Hayat School implements tailored examination methods for CSN, supporting inclusivity in the evaluation process. In conclusion, inclusive educational management requires ongoing professional development for educators, with teaching strategies that enhance empathy and understanding among regular students toward their peers with special needs. These efforts are essential to ensure that CSN develop academically and socially alongside their peers in an inclusive environment.